2009
DOI: 10.1002/bdd.687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of itraconazole on the pharmacokinetics of everolimus administered by different routes in rats

Abstract: The effect of itraconazole on the pharmacokinetics of everolimus was investigated in rats. Ten minutes after an intravenous or intraintestinal administration of itraconazole, everolimus was delivered intravenously (0.2 mg/kg) or intraintestinally (0.5 mg/kg). Blood concentrations of everolimus were measured up to 240 min, and pharmacokinetic parameters were calculated. Intraintestinally administered itraconazole (20 mg/kg) significantly increased the area under the concentration-time curve (AUC) of intraintest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The patient's infection recurred after excision, suggesting that combined surgical and medical therapy may be required to completely eradicate P richardsiae . Importantly, itraconazole, a direct cytochrome P450 3A4 inhibitor, can increase serum levels of calcineurin inhibitors and mammalian target of rapamycin inhibitors, such as everolimus in this patient 7 . Therefore, initiation of antifungal therapy often necessitates the reduction in the dosages of immunosuppressant therapies in transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's infection recurred after excision, suggesting that combined surgical and medical therapy may be required to completely eradicate P richardsiae . Importantly, itraconazole, a direct cytochrome P450 3A4 inhibitor, can increase serum levels of calcineurin inhibitors and mammalian target of rapamycin inhibitors, such as everolimus in this patient 7 . Therefore, initiation of antifungal therapy often necessitates the reduction in the dosages of immunosuppressant therapies in transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that short-term treatment with a high dose of EVR (5 mg/kg for 7 days on days 21-28 post STZ injection when the learning and memory impairments were established) or chronic administration of low (1 mg/kg) or high (5 mg/kg) doses of EVR from day 0 (day of STZ icv injection) to day 20, were able to attenuate STZ-induced learning and memory deficits by inhibiting oxidative stress, amelioration of neuronal injury, and restoration of AChE activity in the hippocampus. The doses and time schedule of the administration of EVR were selected based on preliminary experiments, as well as, previous studies (Russo et al, 2016[ 65 ]; Sanchez-Fructuoso, 2008[ 68 ]; Yokomasu et al, 2009[ 90 ]).…”
Section: Discussionmentioning
confidence: 99%